Awareness of the importance of student inclusion with the use of sign language (Research, Society and Development, 2022)
The present work seeks to contribute to raising awareness about the importance of including students with hearing impairments through the use of Libras in teaching. This work presents a study of the existing legislation on inclusion, the current conditions of teaching, and the importance of inclusive education, highlighting the inclusion of the deaf student. Inclusion is understanding the limitations of the other and providing access, through the implementation of artifice with the purpose of guaranteeing social participation and coexistence based on respect for diversity and individual rights regardless of their disability. As a result, awareness of the importance and urgency of inclusion can be much more productive and effective through communication to the various fields of life, be it society, education, politics, or health. This research identified a lack of legislation and didactic material on the subject and teaching proposals, in general, disjointed, superficial, and incomplete. Here, the issue of including students who have little or no hearing in Physics teaching stands out.